The endophytic fungus Piriformospora indica enhances Arabidopsis thaliana growth and modulates Na+/K+ homeostasis under salt stress conditions. (October 2017) - Abdelaziz, Mohamed E.; Kim, Dongjin; Ali, Shawkat; Fedoroff, Nina V.; Al-Babili, Salim
Highlights: Colonization by Piriformospora indica improves Arabidopsis thaliana growth under salt stress. Piriformospora indica colonized roots showed higher expression of the ion channels HKT1, KAT1 and KAT2 . Piriformospora indica colonization leads to a lower Na + /K + ratio, which may be a result of increased KAT1 and KAT2 expression and explain the enhanced salt tolerance. Abstract: The mutualistic, endophytic fungus Piriformospora indica has been shown to confer biotic and abiotic stress tolerance to host plants. In this study, we investigated the impact of P. indica on the growth of Arabidopsis plants under normal and salt stress conditions. Our results demonstrate that P. indica colonization increases plant biomass, lateral roots density, and chlorophyll content under both conditions. Colonization with P. indica under salt stress was accompanied by a lower Na + /K + ratio and less pronounced accumulation of anthocyanin, compared to control plants. Moreover, P. indica colonized roots under salt stress showed enhanced transcript levels of the genes encoding the high Affinity Potassium Transporter 1 (HKT1) and the inward-rectifying K + channels KAT1 and KAT2, which play key roles in regulating Na + and K + homeostasis. The effect of P. indica colonization on AtHKT1;1 expression was also confirmed in the Arabidopsis line gl1-HKT:AtHKT1;1 that expresses an additional AtHKT1;1 copy driven by the native promoter. Colonization of the gl1-HKT:AtHKT1;1 by P. indica also increased lateral roots density and led to a better Na + /K + ratio, which may be attributed to the observed increase in KAT1 and KAT2 transcript levels. Our findings demonstrate that P. indica colonization promotes Arabidopsis growth under salt stress conditions and that this effect is likely caused by modulation of the expression levels of the major Na + and K + ion channels, which allows establishing a balanced ion homeostasis of Na + /K + under salt stress conditions.